Antioxidant activity, total phenolic and total flavonoid content of 22 Sabah traditional rice varieties - Fui, Fui Lem; Chia, How Yen; Ling, Joanna Siaw Jing; David Devina,; Su, Na Chin; Fong, Tyng Chee (Penerbit Universiti Kebangsaan Malaysia, 2025)
Studies have demonstrated that the traditional rice cultivated in Sabah, East Malaysia, exhibits substantial genetic diversity and is renowned for its outstanding nutritional content. However, there are limited studies to ascertain the antioxidant activity and composition of biochemical substances in it. The present study evaluates the antioxidant properties of 22 Sabah Traditional Rice varieties, which are classified into pigmented and non-pigmented types. An analysis was performed on 22 Sabah Traditional Rice varieties to determine their Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and DPPH assay. In addition, a metabolic profiling analysis was performed on biochemical substances extracted from a specific rice variety, Beras Perang, which is known for its high levels of TPC, TFC, and antioxidant activity. It was observed that pigmented rice possesses high phenolic content, namely Beras Perang and Baragang Merah (semi-polished), with values ranging from 1.300±0.004 to 1.967±0.019 mg GAE/g. For TFC results, Beras Perang, Masuri Hitam and Tadong Biasa (unpolished) showed higher abundance (1.000±0.001, 0.888±0.001 and 0.793±0.003 mg QE/g), respectively. The antioxidant assay results indicate that three varieties, namely Baragang Merah (92.832± 0.651%), Beras Perang (91.916± 0.331%), and Rongguol (91.965± 0.515%) have antioxidant levels exceeding 90%. Beras Perang has the greatest levels of TPC, TFC, and antioxidants. In metabolic profile analysis, Beras Perang contains a specific form of linoleic acid (12-oxo-10Z-octadecenoic acid) which is not present in the negative control. In conclusion, Sabah Traditional Rice exhibits a highly promising antioxidant activity, over 90%, making it a potential candidate for further development as an alternative superfood.